Handbook of international feminisms perspectives on psychology, women, culture, and rights - Rutherford, Alexandra; Capdevila, Rose; Undurti, Vindhya; Palmary,Ingrid (Springer eBooks., 2011)
This handbook presents the histories, status, and contours of feminist research and practice in regional and/or national contexts. Global experts present their perspectives on women, culture, and rights to illuminate the diverse forms of feminist psychological work.